Le Corbusier and Crowds: Un centre national de réjouissances populaires de 100, 000 participants, 1936. Issue 2 (4th May 2019) - Mackay, Toby; Brott, Simone
Abstract: In 1936, Le Corbusier proposed his first stadium, which he entitled a Centre national de réjouissances populaires de 100, 000 participants . It was a spectacular cultural, sporting, and political vision for Paris as it was to hold 100, 000 spectators. This was his first project to deal with architecture's relationship with the crowd, and through Elias Canetti's definition of the closed vs. open crowd, this paper investigates how Le Corbusier treated and understood the crowd through its relationship not only with the spectacle immediately in front of it in the stadium, but also with its relationship to national identity and politics outside the arena.